RANCANG BANGUN MULTIMEDIA PEMBELAJARAN INTERAKTIF MEDIA PENYIMPANAN (HARDDISK) MENGGUNAKAN ADOBE FLASH CS3 PADA SISWA KELAS X SMK NEGERI 1 MAGELANG - Ali Machmudi, Moch; Wahyu Arista, Diko; Wahyudiono, Sugeng (STMIK BINA PATRIA, 2026)
The aim of this study is to design an interactive learning system that can be used to effectively and efficiently teach students, providing up-to-date information, facilitating learning and being user-friendly. The learning media was designed using Adobe Flash CS3.The research methodology used in this thesis is Research and Development (R&D), which is a method of developing new products or improving existing ones. The method used by the author for developing the system is ADDIE.The design of the learning media includes environmental analysis, interface design, creation of the learning media, testing with students and evaluation of the results.The results of this study show that the interactive learning media can help students to obtain materials more easily and in a more engaging way, thus improving their learning outcomes. Keywords: Interactive Learning Media, Research and Development (R&D), ADDIE, Adobe Flash CS3